Respostas

2014-07-18T18:35:09-03:00
A) x² + 5x + 6 = 0
Δ = b² - 4ac
Δ = 5² - 4 . 1 . 6
Δ = 25 - 24
Δ = 1
x = - b +- √Δ
          2a
x = - 5 +- √1
        2 . 1
x = - 5 +- 1
          2
x' = - 5 + 1 = - 4 : 2 = - 2 = - 2
          2         2  : 2     1
x" = - 5 - 1 = - 6 : 2 = - 3 = - 3
          2         2  : 2    1
S = {- 2, - 3}

b) x² + 18x + 81 = 0
Δ = b² - 4ac
Δ = 18² - 4 . 1 . 81
Δ = 324 - 324
Δ = 0
x = - b +- √Δ
          2a
x = - 18 +- √0
         2 . 1
x = - 18 +- 0
           2
x' = - 18 + 0 = - 18 : 2 = - 9 = - 9
           2          2   : 2     1
x" = - 18 - 0 = - 18 : 2 = - 9 = - 9
          2           2   : 2     1
S = {- 9}

c) x² - 20x + 100 = 0
Δ = b² - 4ac
Δ = - 20² - 4 . 1 . 100
Δ = 400 - 400
Δ = 0
x = - b +- √Δ
         2a
x = - (- 20) +- √0
          2 . 1
x = 20 +- 0
         2
x' = 20 + 0 = 20 : 2 = 10 = 10
          2        2  : 2     1
x" = 20 - 0 = 20 : 2 = 10 = 10
         2         2  : 2     1
S = {10}
1 5 1